Leviathan. Thomas Hobbes. - Flathman, Richard E. and David Johnston (New York W.W. Norton and Company, 1997)
This Norton Critical Edition of arguably the greatest work of political theory written in the English language contains the bulk of Hobbes treatise, including all chapters except those which are of interest primary to professional historical scholars. To make Hobbes sometimes archaic prose more accessible to students, the editors have included explanatory annotations throughout.
Keywords: Philosophy